2018
DOI: 10.1159/000494254
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary insights on the relation between endometriosis, pelvic pain, and employment

Abstract: Aims: The economic burden of endometriosis and pelvic pain involves direct and indirect healthcare costs due to work loss and decreased productivity. However, the relation between endometriosis, pelvic pain, and employment remains underinvestigated. This study aimed at providing preliminary insights into this topic. Methods: We compared the employment status (having vs. not having a job) in 298 consecutive endometriosis patients and in 332 women without a history of endometriosis (control group). We also exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…A study of 630 women consecutively recruited at a tertiary endometriosis research center in Italy reported that women with symptomatic endometriosis were significantly less likely to be employed compared with women without endometriosis (OR, 0.35 [95% CI, 0.18-0.65]) or women with asymptomatic endometriosis (OR, 0.36 [95% CI, 0.17-0.79]). 54 Unemployed women with endometriosis had a greater severity of dysmenorrhea, dyspareunia, chronic pelvic pain, and dyschezia compared with employed women with endometriosis.…”
Section: Employment and Careermentioning
confidence: 90%
See 1 more Smart Citation
“…A study of 630 women consecutively recruited at a tertiary endometriosis research center in Italy reported that women with symptomatic endometriosis were significantly less likely to be employed compared with women without endometriosis (OR, 0.35 [95% CI, 0.18-0.65]) or women with asymptomatic endometriosis (OR, 0.36 [95% CI, 0.17-0.79]). 54 Unemployed women with endometriosis had a greater severity of dysmenorrhea, dyspareunia, chronic pelvic pain, and dyschezia compared with employed women with endometriosis.…”
Section: Employment and Careermentioning
confidence: 90%
“…We identified 15 studies in women with endometriosis that address the impact of endometriosis on the employment and career components of the life course. 11,28,32,34,35,41,[51][52][53][54][55][56][57][58][59] This included eight cross-sectional studies in Europe and the United States that reported a considerable deleterious influence of endometriosis on work productivity and capacity as well as career and salary growth. 11,35,41,[51][52][53]55,56 Using an established registry, Fourquet et al 52 conducted a survey to assess outcomes in 107 women with selfreported, surgically diagnosed endometriosis.…”
Section: Employment and Careermentioning
confidence: 99%
“…A priori, based on directed Acyclic graphs (DAGs) and the existing literature, we selected the following relevant potential confounding factors: maternal age, smoking, body mass index (BMI), and socioeconomic status. These factors have been shown to be associated with endometriosis [14][15][16] and increase the risk of several adverse pregnancy outcomes [17][18][19][20]. Thus, we considered these the most important potential confounders.…”
Section: Assessment Of Biasmentioning
confidence: 99%
“…Previous studies suggest that the role of endometriosis on women's ability to work is undermined. 4,[7][8][9][10][11] Using a modified Work Ability Index (WAI), a Danish case-control study showed that women with endometriosis aged 26-35 years reported poorer work ability and more sick days than women without endometriosis. 10 Other studies using the Work Productivity and Activity Impairment (WPAI) questionnaire indicate that women with endometriosis report major losses regarding hours of missed work, impairment of work tasks, productivity losses and impairment of daily life activities.…”
Section: Introductionmentioning
confidence: 99%
“…9,11 Concerning employment status, cross-sectional case-control studies suggest that women with endometriosis are less likely to be employed and practicing their desired profession. 4,8 A longitudinal case-control study in the USA evaluated endometriosis-related exits from the workforce and found increased risks of sick leave and short-term disability. 12 However, although previous studies quite unanimously agree that endometriosis has adverse effects on work life, the evidence remains limited, as all but one study 12 utilize self-reported data and crosssectional designs and mainly cover the years of fertility.…”
Section: Introductionmentioning
confidence: 99%